Fructose levels are elevated in women with polycystic ovary syndrome with obesity and hyperinsulinemia. Issue 1 (14th January 2020) - Shi, Bei; Feng, Di; Sagnelli, Matthew; Jiao, Jiao; Sun, Xiaoli; Wang, Xiuxia; Li, Da
Abstract: STUDY QUESTION: Are fructose levels altered in women with polycystic ovary syndrome (PCOS)? SUMMARY ANSWER: Elevated serum fructose levels are associated with PCOS in Chinese Han women with overweight/obesity and hyperinsulinemia, and fructose levels are higher in follicular fluids from PCOS patients than from control subjects. WHAT IS KNOWN ALREADY: Both fructose levels and PCOS are closely linked to obesity and insulin resistance. However, the relationship between fructose and PCOS remains largely unknown. STUDY DESIGN, SIZE, DURATION: A total of 157 Chinese Han women (67 controls and 90 PCOS patients) were recruited at Shengjing Hospital of China Medical University. To systematically study the relationship between serum fructose levels and PCOS, the study population of control subjects and PCOS patients was divided into overweight/obese and lean subgroups, and hyper-fasting serum insulin (FSI) and normal-FSI subgroups, respectively. PARTICIPANTS/MATERIALS, SETTING, METHODS: Fructose levels were measured in serum samples collected from 80 patients with PCOS (32 lean, 48 overweight/obese) and 59 control subjects (27 lean, 32 overweight/obese) and in follicular fluid samples collected from mature follicles (17–22 mm) and matched immature follicles (8–13 mm) from 10 patients with PCOS and 8 control subjects. MAIN RESULTS AND THE ROLE OF CHANCE: Serum fructose levels were increased in overweight/obese and hyper-FSI PCOS patients compared with the control subjects. Fructose had an area under the curve (AUC) of 79.7% at a cutoff value of 10.13 pmol/μl, with a sensitivity of 91.7% and a specificity of 59.3% for the prediction of PCOS in overweight/obese patients. In the hyper-FSI group, fructose had an AUC of 72% at a cutoff value of 10.49 pmol/μl, with a sensitivity of 71.1% and a specificity of 64.4% for the prediction of PCOS. There were no differences between fructose, total testosterone, free testosterone or dehydroepiandrosterone sulfate levels with respect to the reliability of predicting PCOS in the overweight/obese or hyper-FSI groups using the method outlined by Hanley and McNeil. Notably, the combination of fructose and total testosterone levels resulted in the highest AUC of 86.0% and high sensitivity (85.4%) and specificity (83.1%) for the prediction of PCOS in overweight/obese patients. The positive predictive value (PPV) and negative predictive value (NPV) were 80.4 and 87.5%, respectively. Similarly, the combination of fructose and total testosterone levels also resulted in a high AUC of 80.2% and moderate sensitivity (73.3%) and high specificity (84.7%) for the prediction of PCOS in hyper-FSI patients. The PPV and NPV were 78.6 and 80.6%, respectively. Furthermore, fructose levels were significantly higher in follicular fluids from PCOS patients than from control subjects, regardless of whether the follicles were mature or immature. LIMITATIONS, REASONS FOR CAUTION: It remains unclear whether fructose levels contribute directly to follicular development and the pathogenesis of PCOS or are merely a biomarker of these processes. WIDER IMPLICATIONS OF THE FINDINGS: The results of the present study, together with our previous study, show that monosaccharide status may be a novel marker for PCOS, highlighting the importance of further investigation into the role of monosaccharides, especially fructose, in the pathogenesis of PCOS. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the National Natural Science Foundation of China (No. 81671423 and No. 81402130), the National Key Research and Development Program of China (No. 2018YFC1003100), Liaoning Provincial Key Research and Development Program (No. 2018225090), the Fok Ying Tung Education Foundation (No. 151039), Distinguished Talent Program of Shengjing Hospital (No. ME76) and Distinguished Teacher Program of China Medical University (No. QGZ2018079). No competing interests were declared.